(untitled) (Sains Humanika, 2015)
This study is done to know whether the judges’ ratings results in the same decisions for candidates of the same ability and to show the relative severity of the different judges. The Many-facets Rasch Measuring Model (MFRM) is used in this study to determine the validity and reliability of raters’ severity and leniency. The research involves five raters and fifty examinees from standard five students of a primary school in Butterworth. There are five science process skills evaluated that is the observation, classifying, measuring, relationship between space and time and experimenting (identifying variables, make hypothesis, presenting the report). The results of this study suggest that raters of science process skills performance such as those in the PEKA can be trained to rate appropriately and consistently, and that under a system of double marking, assigning different raters to different test takers does not pose a threat to the validity of scores, and that tests are valid, reliable, and fair in that regard.